2022
DOI: 10.3390/ijerph191610027
|View full text |Cite
|
Sign up to set email alerts
|

Is Working from Home during COVID-19 Associated with Increased Sports Participation? Contexts of Sports, Sports Location and Socioeconomic Inequality

Abstract: Previous research has focused mainly on the association between working from home (WFH) and physical activity, establishing that physical activity diminished among people WFH during the COVID-19 pandemic. In our study, we investigated the association between WFH and specifically sports participation (competitive and non-competitive). We theorized that WFH would offer individuals additional opportunities to practice sports during the pandemic. Governmental restrictions at the time constrained opportunities to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…First, a novel perspective might be that young workers nowadays react differently to mechanisms and concepts that have been important for a long time. The rise of working from home [65], burnout, and lower well-being [78] as well as the centrality of leisure instead of work among these young adults [73] calls for innovative research on the consequences of working conditions among this group. These young workers will constitute the labour force for the next decennia, and thus suitable knowledge regarding their behaviour and preferences is vital to create and maintain a healthy workforce.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a novel perspective might be that young workers nowadays react differently to mechanisms and concepts that have been important for a long time. The rise of working from home [65], burnout, and lower well-being [78] as well as the centrality of leisure instead of work among these young adults [73] calls for innovative research on the consequences of working conditions among this group. These young workers will constitute the labour force for the next decennia, and thus suitable knowledge regarding their behaviour and preferences is vital to create and maintain a healthy workforce.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In other words, having worktime and work location control offers more flexible options to plan leisure time, as it relaxes temporal and areal restrictions, which makes participation in sports easier and facilitates compensation for workload through sports [63][64][65]. This suggests that flexibility in worktime and work location mitigates the consequences of cognitive job demand overload, which may give workers more opportunities and energy to participate in sports [65,66]. For this reason, we expect that (H3): Hypothesis 3.…”
Section: Moderation Of the Cognitive Job Demands And Sports Participa...mentioning
confidence: 96%
See 1 more Smart Citation
“…However, persons WFH in the Netherlands during the pandemic reported good health and fewer musculoskeletal disorders than before [48]. Besides, Grubben et al found WFH to be positively associated with sports participation [58]. On their part, Hallman et al revealed that workers in Sweden slept more when they worked from home, potentially leading to health benefits [59].…”
Section: Wellbeingmentioning
confidence: 99%